Advancing sales theory through a holistic view: how social structures frame selling. Issue 4 (1st October 2020) - Hartmann, Nathaniel N.; Wieland, Heiko; Vargo, Stephen L.; Ahearne, Michael
Abstract: Sales research is increasingly recognizing the blending of salesperson responsibilities, the growing number of interactions involved in sales processes and activities, and the nonlinear nature of value (co)creation. This has resulted in a shift towards more holistic and systemic views to explain selling and sales related phenomena. We adopt such a view to examine broader social structures and argue that recognizing their overlapping and nested nature is important to understanding sales processes. To aid the investigation of social structure and theorizing more generally, the practice of examining levels of aggregation and theoretical abstraction is introduced. This practice can also in the framing of articles and identification of their contributions to the sales and broader literature.